2005
DOI: 10.1182/blood-2004-09-3567
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor activity in whole blood

Abstract: Tissue factor (TF) is an integral membrane protein essential for hemostasis. During the past several years, a number of studies have suggested that physiologically active TF circulates in blood at concentrations greater than 30 pM either as a component of blood cells and microparticles or as a soluble plasma protein. In our studies using contact pathway-inhibited blood or plasma containing activated platelets, typically no clot is observed for 20 minutes in the absence of exogenous TF. An inhibitory anti-TF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
204
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(221 citation statements)
references
References 55 publications
16
204
1
Order By: Relevance
“…The removal of 20K pellets and 100K pellets revealed a reduced activity of PPL in the subsequent supernatants (Figure 5), similar to findings by Marchetti et al [15]. Our findings indicated that EVs from healthy persons carry no or a very low amounts of TF, but contain some PPL which is also in agreement with the findings of others [28,29]. …”
Section: Discussionsupporting
confidence: 92%
“…The removal of 20K pellets and 100K pellets revealed a reduced activity of PPL in the subsequent supernatants (Figure 5), similar to findings by Marchetti et al [15]. Our findings indicated that EVs from healthy persons carry no or a very low amounts of TF, but contain some PPL which is also in agreement with the findings of others [28,29]. …”
Section: Discussionsupporting
confidence: 92%
“…Expression of cell surface-and microparticle-associated TF by LPS-stimulated THP-1 cells was confirmed by flow cytometry (data not shown). The percentage P-selectin-positive platelets that stained positively for TF when incubated in the presence of THP-1 cells and LPS (1.2% Ϯ 0.6%) was virtually identical to that observed in the absence of LPS (2.4% Ϯ 1.1%; Figure 1B), confirming previous observations made in whole blood 6,7 and suggesting that TF on monocytes or monocyte-derived microparticles is not transferred to platelets.…”
Section: No Evidence For Tissue Factor On Plateletssupporting
confidence: 78%
“…This paradigm has been challenged by studies suggesting that platelets express active TF after de novo synthesis, 2,3 transfer from monocytes, 4 or release from ␣-granules. 5 In other studies, 6,7 however, the existence of platelet TF could not be demonstrated.…”
Section: No Evidence For Tissue Factor On Plateletsmentioning
confidence: 91%
See 2 more Smart Citations